Determination of internal loss and quasi-fermi level separation from the amplified spontaneous emission (ASE) spectrum of Fabry-Perot (FP) semiconductor lasers - DONEGAN, JOHN FRANCIS (IEEE, 2006)
The net modal gain and the un-amplified spontaneous emission (ASE) coupled into the laser waveguide mode are extracted from the ASE spectrum of Fabry?PErot semiconductor lasers by the Fourier transform method with a deconvolution process. Highly accurate quasi-Fermi level separation and internal loss are then derived by a minimum search process from the relationship between the spontaneous emission and gain.
PUBLISHED
Keywords: Amplified spontaneous emission; Fabry?Perot (FP) semiconductor laser